Corporate Crime and the Discourse of Socio-Environmental Responsibility: The Good, the Ugly, and the Perfumed - de Souza, Lionardo D. (2017)
The critiques to the notion of corporate social responsibility establish that it is an ideological movement used to legitimize the power of large corporations. This research analyses social responsibility discourses of a corporation that has been the protagonist of an environmental crime, aiming to identify the relationship between what is declared or preached and what is practiced. Because it is a documentary investigation, methodologically, files of the company and the Mayor's Office of the municipality where the crime occurred were studied. It was found that the company uses the discourse of socio-environmental responsibility to hide undue practices that harm the environment and the community; meaning that, in order not to be considered a bad or ugly corporation, it perfumes its practices with natural environment protection discourses.